Maintaining leachate flow through a leach bed reactor during anaerobic digestion of high-solids cattle manure - Lewis, Matthew A., author; Sharvelle, Sybil, advisor; Grigg, Neil, committee member; Quinn, Jason, committee member (Colorado State University. Libraries, 2018)
To address the accumulation of high-solids cattle manure (HSCM) found at many of the state's Animal Feeding Operations (AFOs), researchers at CSU have developed a Multi-Stage Anaerobic Digester (MSAD). The MSAD system consists of a leach bed reactor (LBR), a compositing tank, and a fixed-film methanogenic reactor. The LBR is a critical part of the MSAD system since hydrolysis can be a rate-limiting step in the anaerobic digestion of HSCM (Hinds 2015; Veeken and Hamelers 1999). To ensure that hydrolysis is occurring properly within the reactor, leachate injection and reactor operation must proceed in a manner that facilitates uniform distribution of leachate through the manure waste bed. Since the leachate must be recirculated through the LBR for the entirety of the batch digestion time, any phenomena that disrupt the duration or uniformity of leachate distribution must be addressed. The overarching goal of this thesis project was to improve the hydraulic performance of the LBR stage of the MSAD. This research included a multi-criterion decision analysis (MCDA) to assess unique design aspects of the MSAD relative to other technologies, construction and operation of a prototype LBR, and the development of an experimentation strategy to assess mechanism of hydraulic failure in the LBR. The MSAD system was compared to four other high-solids anaerobic digester technologies using a MCDA. The purpose of this comparison was to identify unique design features of the MSAD technology compared to other high-solids anaerobic digestion technologies to inform the focus of future design and research activities. The technologies were rated and evaluated for the following criteria: operational requirements, impact of hydraulic failure, capital requirements, operational control, feedstock technology fit, and process efficiency. The scores ranged from 2.9 to 3.7 out of 5 possible points. Under equal criteria weighting, the MSAD system received the highest rating with a score of 3.7. The MSAD system received high ratings due to its strong hydraulic performance, operational control, and process efficiency. Knowledge gained through laboratory and prototype-scale LBR experimentation was used to establish possible improvements to LBR design. The primary improvement to the LBR was the modification from a downflow to an upflow configuration. A prototype LBR was operated in the upflow configuration to facilitate longer durations of undisrupted leachate permeation. In addition, it was determined that leachate injection spacing should be studied further as results from operation of the prototype LBR suggested that higher volatile solids reduction occurred closer to the leachate influent manifold. Column experiments and prototype operation showed some successful operation of LBRs for treating HSCM. However, hydraulic failures due to clogging and preferential pathway formation were observed. Due to the continued risk of hydraulic failure, further research was needed to understand mechanisms for hydraulic failure and to determine approaches to overcome these issues. At commercial scale, hydraulic failure of LBRs would result in decreased energy and agricultural product output and increased operating costs. Since commercial processes rely on reproducible results, a high degree of LBR reliability is required to achieve technical and economic feasibility. Therefore, control over the hydraulic performance of LBRs is critical for commercialization of the MSAD system. To this end, an experimentation strategy was developed, with the goal to elucidate the mechanisms behind hydraulic failures occurring in the LBR. To evaluate these mechanisms, the experimentation strategy recommends the use of electrical resistivity tomography (ERT) to render visualizations of leachate distribution throughout the waste bed. Further characterization of the pore space network geometry at the microscale using either Magnetic Resonance Imaging (MRI) or X-ray Computed Tomography (X-ray CT) is recommended.
Keywords: biogas; hydraulic conductivity; renewable energy; high-solids; anaerobic digestion; leachate